METHANE GHG EMISSION ANALYSIS SUPPORTS REGIONAL ACTION PLANS FOR MITIGATION AND ADAPTATION TO THE IMPACTS OF CLIMATE CHANGE IN SITUBONDO REGENCY - Thohiron, Mochamad; Hassan, Faez M.; Susilo, Achmadi; Suryaningsih, Dwie Retna; Wicaksono, Achmad (Yayasan Education and Social Center, 2024)
The study aims to inventory and analyze GHG methane (CH4) emissions to support RAD in mitigation and adaptation of PI Situbondo Regency. It is hoped that the results of the research can be used as input for the Regional Government in designing implementable mitigation and adaptation actions. The scope of the research in the Situbondo Regency area was six months. Research methods: 1) Tier-1 IPCC Guidlines (IPCC, 2006) for numerical equation analysis of methane gas, and 2) analysis of remote sensing and numerical spatial data on cloud-based digital platform Java script Google Earth Engine (GEE) and Google Colaboratory Research (GColab) 2023, image digitization and outlating in QGIS software. Research data: 1) activity data based on producing sectors, methane emission factors, and farmer group mitigation options questionnaires; and 2) remote sensing data access to the methane gas datasets Sentinel-5P OFFL CH4: Offline Methane, and MOD11A1.061 Terra Land Surface Temperature and Emissivity Daily Global 1km. Research results: the transportation sector emits the highest methane gas (tons of CO2 eq) at 378,486; agriculture 249,580.74; industrial energy 30,533.58; and the lowest livestock 6,364. Remote sensing results: an increase in methane gas emissions during the analysis period. The lowest CH4 gas emissions were respectively in 2017, 2019 and 2021, respectively 0.74 g/m2; 1.79 g/m2; and 1.85 g/m2; and the highest respectively at 4.56 g/m2; 10.95 g/m2; and 23.90 g/m2 in the same year. The lowest temperature increased in 2017, 2019, then decreased in 2021 to 19oC, 21oC and 18oC respectively. The highest temperature increased in 2017, 2019, and decreased in 2021 respectively 39oC, 40oC and 38oC. Increasing methane gas emissions are correlated with the lowest and highest LST from 2017-2021 with a correlation of R ≥ 0.6 (0.6-0.9).